Association of prognostic nutritional index with all-cause mortality and cardiovascular mortality: a nationwide population-based cohort study - Zhou, Ce; Zhou, You; Wang, TingYue; Wang, Yun; Liang, XiuYi; Kuang, Xin (Frontiers in Nutrition, 2025)
BackgroundThe prognostic nutritional index (PNI) has shown prognostic value in various diseases, but its association with mortality in the general population remains unclear.MethodsWe analyzed data from 30,741 adults in the National Health and Nutrition Examination Survey (NHANES) 2007–2018. Cox proportional hazard models examined the association between PNI and mortality outcomes. Restricted cubic spline analyses were performed to assess non-linear relationships. Subgroup analyses were conducted to evaluate effect modifications.ResultsDuring follow-up, higher PNI values were associated with lower all-cause mortality (HR: 0.95, 95% CI: 0.94–0.96) and cardiovascular mortality (HR: 0.94, 95% CI: 0.93–0.96). Non-linear relationships were identified with threshold effects at PNI = 50.24 for all-cause mortality and PNI = 51.50 for cardiovascular mortality. The protective associations were particularly strong among participants with liver disease (P for interaction < 0.001).ConclusionPrognostic nutritional index demonstrates significant predictive value for mortality outcomes in the general U.S. adult population, with identified threshold effects. These findings suggest PNI’s potential utility as a valuable risk stratification tool in clinical practice.